Is There an Association or Not?—Investigating the Association of Depressiveness, Physical Activity, Body Composition and Sleep With Mediators of Inflammation - Schmidt, Frank M.; Mergl, Roland; Minkwitz, Juliane; Holdt, Lesca M.; Teupser, Daniel; Hegerl, Ulrich; Himmerich, Hubertus; Sander, Christian (Frontiers in Psychiatry, 2020)
Background: Cytokines are a category of heterogeneous mediators of inflammation that contribute to a low-grade inflammation in different disorders like major depression and obesity. Apart from responses to inflammation, infection and trauma, it still remains unclear which social, psychological and medical factors reliably interact with cytokine regulation. In the current investigation, the association between anthropometrics, depressiveness, physical activity and parameters of sleep on the one side, and levels of pro-and anti-inflammatory cytokines on the other, were investigated in a sample of community-dwelled adults at two different time points. Methods: Data sets of 49 subjects from the OBDEP project (Obesity and Depression: pathogenic role of sleep and wakefulness regulation, motor activity level and neurochemical aspects), were available for analysis. Serum cytokine measures included interleukin (IL)-2, IL-4, IL-5, IL-10, IL-12, IL-13, GM-CSF, IFN-γ and TNF-α, anthropometrics were assessed via physical examination, depressiveness was assessed via BDI2, parameters of physical activity (steps, METs) and sleep (night/total sleep duration) were measured via a 1-week actigraphy. All parameters were assessed at baseline (T1) and following a non-interventional mean interval of 215 days (T2). Results: Regression analyses for T1 revealed that BDI2 score was the best positive predictor for the concentrations of all nine cytokines. Furthermore, the number of steps and the nightsleep duration were significantly negatively associated with some of the cytokines. At T2, the amount of steps was found to negatively associated with IL-4, IL5, IL-10, GM-CSF, IFN-γ and TNF-α, whereas the BMI could significantly predict IL-12 and IL-13. In contrast to T1, the BDI2-score was not significantly associated with any of the cytokines. No associations could be found between dynamics in cytokines from T1 and T2 and changes in any of the bio-psycho-social variables. Discussion: The present results underpin the role of physical activity, subjective well-being and body composition on inflammatory mediators. However, since the results only showed a reasonable within-subjects-replicability, the conclusions for an association with the parameters cannot be generalized for community-dwelled samples. Without an intervention program, changes in cytokine concentrations appear independent from casual alterations in the bio-psycho-social parameters.